Контрольный выброс: [фантастический роман] / А. Л. Ливадный - Ливадный Андрей (S.T.A.L.K.E.R., 2009)
Экземпляры: ф. 6 (20151102) / Инвентарный номер: 60503 / Цена: 80.00 / Авт.знак: Л 55 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-445